On the shock performance of a nonlinear vibration isolator with high-static-low-dynamic-stiffness - Tang, Bin; Brennan, M. J. [UNESP] (Elsevier B.V., 2014)
The vibration isolation characteristics of a high-static-low-dynamic-stiffness (HSLDS) isolator, which has geometrically nonlinear stiffness, have been well established both theoretically and experimentally in the recent literature. However, the shock isolation characteristics of such an isolator subject to base excitation are not currently known. In this paper, these characteristics are determined for two illustrative inputs, which are a rounded step and a versed sine displacement, using a simple model of the isolator comprising a vertical spring coupled to two horizontal springs. The isolator is configured to reduce the dynamic stiffness of the isolator and hence increase the frequency range of isolation. The shock responses of the isolator are determined analytically for low levels of excitation, and numerically for high levels of excitation. It is found that when the shock amplitude is small, the nonlinearity is beneficial, and that the quasi-zero stiffness isolator has the best shock performance in terms of the smallest displacement and acceleration of the suspended mass. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Shock isolation; Geometric nonlinear stiffness; Rounded step displacement; Versed sine displacement